Integration of cloud computing with Internet of things : foundations, analytics, and applications - Mangla, Monika; Satpathy, Suneeta; Nayak, Bhagirathi, 1963-; Mohanty, Sachi Nandan (John Wiley & Sons, Inc., 2021)
"The book aims to integrate the aspects of IoT, Cloud computing and data analytics from diversified perspectives. The book also plans to discuss the recent research trends and advanced topics in the field which will be of interest to academicians and researchers working in this area. Thus, the book intends to help its readers to understand and explore the spectrum of applications of IoT, cloud computing and data analytics. Here, it is also worth mentioning that the book is believed to draw attention on the applications of said technology in various disciplines in order to obtain enhanced understanding of the readers. Also, this book focuses on the researches and challenges in the domain of IoT, Cloud computing and Data analytics from perspectives of various stakeholders."--